Daily leptin blunts marrow fat but does not impact bone mass in calorie-restricted mice. Issue 3 (June 2016) - Devlin, M J; Brooks, D J; Conlon, C; Vliet, M van; Louis, L; Rosen, C J; Bouxsein, M L
Abstract : Starvation induces low bone mass and high bone marrow adiposity in humans, but the underlying mechanisms are poorly understood. The adipokine leptin falls in starvation, suggesting that hypoleptinemia may be a link between negative energy balance, bone marrow fat accumulation, and impaired skeletal acquisition. In that case, treating mice with leptin during caloric restriction (CR) should reduce marrow adipose tissue (MAT) and improve bone mass. To test this hypothesis, female C57Bl/6J mice were fed a 30% CR or normal (N) diet from 5 to 10 weeks of age, with daily injections of vehicle (VEH), 1mg/kg leptin (LEP1), or 2mg/kg leptin (LEP2) ( N =6–8/group). Outcomes included body mass, body fat percentage, and whole-body bone mineral density (BMD) via peripheral dual-energy X-ray absorptiometry, cortical and trabecular microarchitecture via microcomputed tomography (μCT), and MAT volume via μCT of osmium tetroxide-stained bones. Overall, CR mice had lower body mass, body fat percentage, BMD, and cortical bone area fraction, but more connected trabeculae, vs N mice ( P< 0.05 for all). Most significantly, although MAT was elevated in CR vs N overall, leptin treatment blunted MAT formation in CR mice by 50% vs VEH ( P< 0.05 for both leptin doses). CR LEP2 mice weighed less vs CR VEH mice at 9–10 weeks of age ( P< 0.05), but leptin treatment did not affect body fat percentage, BMD, or bone microarchitecture within either diet. These data demonstrate that once daily leptin bolus during CR inhibits bone marrow adipose expansion without affecting bone mass acquisition, suggesting that leptin has distinct effects on starvation-induced bone marrow fat formation and skeletal acquisition.